CASA real-time multi-Doppler retrieval system - Zhang, Sean X., author; Chandrasekaran, V., advisor; Bringi, V. N., committee member; Jayasumana, Anura P., committee member; Mielke, Paul W., committee member (Colorado State University. Libraries, 2011)
Doppler synthesis of 3D wind products is of great practical importance to observing and understanding severe weather features such as tornadoes and microbursts. It becomes very effective for severe weather events if this modeling can be performed in real-time. A real-time multi-Doppler retrieval system forms an important product of modern weather radar networks. Challenging constraints exists between computing performance, high data resolution, and other quality issues. This Thesis describes the implementation of the operational Real-time Multi-Doppler Retrieval System (R-MDRS) of the Center for Collaborative Adaptive Sensing of the Atmosphere Engineering Research Center (CASA ERC). The R-MDRS is seamlessly integrated into CASA's Distributed Collaborative Adaptive Sensing (DCAS) operational framework and exhibit robust performance that strikes balance between high resolution and real-time processing speeds. A detailed technical description of the CASA R-MDRS implementation is given, including design approach that builds around two core components of the tool: interpolation to a common grid and Doppler synthesis. The R-MDRS generates 3D Wind products in step with network scanning modes and has been effective at detecting convective cells and tornadic activities. Data from 2009 and 2010 weather events are presented and analyzed for evaluating processing time as well as factors that effect data accuracy. These factors include Dual-Doppler candidate pair selection, advection correction, and variations in wind calculation techniques.
Keywords: 3D wind; CASA; DCAS; Doppler; real-time; real-time Doppler retrieval